(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
During the years of independence, in the general education system in the physical education of youth, special attention was paid to sports; specially equipped sports facilities were built and provided with additional sports equipment. Sports competitions were regularly held among secondary school students across the country. Schoolchildren of the Kashkadarya region achieved high results in wrestling, football and volleyball competitions.